Analisis Pengendalian Persediaan Bahan Baku dengan Metode Material Requirement Planning pada Sosis Solo Gajahan di Surakarta - Aurel Yulita Pradyasari; Erni Widajanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sosis Solo Gajahan is a business operating in the food industry, the problem faced by the company is whether the control of raw material inventory for Sosis Solo Gajahan is efficient and whether the application of the Material Requirement Planning (MRP) method can streamline the cost of raw material inventory for Sosis Solo Gajahan. The aim of this research is to consider the company's efficiency in raw material inventory costs and can be used to make decisions related to the efficiency of raw material inventory costs. By using the Material Requirement Planning (MRP) method which consists of the Lot For Lot (LFL), Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods. Based on the results of the total cost calculation according to company policy of IDR 5,131,580 and based on the Material Requirement Planning (MRP) method, which consists of the Lot For Lot (LFL) technique of IDR 696,000, the Economic Order Quantity (EOQ) technique of IDR 1,290,360, and the Period Order Quantity (POQ) technique of IDR 696,000, the researchers concluded that the most efficient method applied at Sosis Solo Gajahan was the Lot For Lot (LFL) and Period Order Quantity (POQ) methods. The Lot For Lot (LFL) method produces inventory costs of IDR 696,000 and the Period Order Quantity (POQ) method produces inventory costs of IDR 696,000 and it is best to calculate raw material inventory control costs using the Material Requirement Planning (MRP) method with the Lot For Lot technique ( LFL) and Period Order Quantity (POQ) techniques, because they can achieve efficient raw material purchasing costs compared to current company policies.